Recorriendo virtual de la Universidad Técnica Estatal de Quevedo Campus "Manuel Haz Álvarez". año 2018 - César Leyton (2018)
The present reseanch called virtual your and is impact on the users of the state techinical University of Quevedo, Manual Haz álvarez. applied different activities and techniques among which stand out, know the difeerent estates throughout the establishmente to salve thle logistical difficulties prsent.......................................